Ring-opening polymerization of ε-caprolactone initiated by tin(II) octoate/n-hexanol: DSC isoconversional kinetics analysis and polymer synthesis - Winita Punyodom; Wanich Limwanich; Puttinan Meepowpan; Boontharika Thapsukhon (Designed Monomers and Polymers, 2021)
The kinetics of ring-opening polymerization (ROP) of ε-caprolactone (ε-CL) initiated by 1.0, 1.5 and 2.0 mol% of stannous(II) octoate/n-hexanol (Sn(Oct)2/n-HexOH) wase successfully studied by non-isothermal differential scanning calorimetry (DSC) at heating rates of 5, 10, 15 and 20 °C/min. The DSC polymerization kinetic parameters of ε-CL were calculated using differential (Friedman) and integral isoconversional methods (Kissinger-Akahira-Sunose, KAS). The average activation energy (Ea) values obtained from Friedman and KAS methods were in the range of 64.9–70.5 kJ/mol and 64.9–80.4 kJ/mol, respectively. The values of frequency factor (A) were determined from model fitting method using Avrami-Erofeev reaction model. The average values of A for the ROP of ε-CL initiated by 1.0, 1.5 and 2.0 mol% of Sn(Oct)2/n-HexOH (1:2) were 7.3x107, 2.8x106 and 1.2x106 min−1, respectively. From kinetics studied, the polymerization rate of ε-CL increased with increasing initiator concentration. The performance of Sn(Oct)2/n-HexOH in the synthesis of poly(ε-caprolactone) (PCL) was investigated by bulk polymerization at temperatures of 140, 160 and 180 °C. Sn(Oct)2/n-HexOH (1:2) could produce high number average molecular weight ($$\overline {{M_{\rm{n}}}} $$= 9.0 × 104 g/mol) and %yield (89%) of PCL in a short period of time at Sn(Oct)2 concentration of 0.1 mol% and temperature of 160°C. The mechanism of the ROP of ε-CL with Sn(Oct)2/n-HexOH was proposed through the coordination-insertion mechanism.